Employee responsiveness towards customer at Telekom Malaysia (Consumer Sales) in Kota Kinabalu / Rozianah Kulin - Kulin, Rozianah (2010)
The aim of this research is to study the responsiveness of employees towards its customer at TM (Consumer Sales). Besides that, it is to identify TM customer satisfaction towards the service that had been given and to suggest recommendation to improve employee responsiveness. There are 120 respondents that divided into two segments which are public higher learning student (UiTM, UMS, Cosmopoint) and working people (government and private sector). Data gathered from fieldworks and analyzed using statistically package of social science (SPSS).